2023
DOI: 10.3390/ijgi12020035
|View full text |Cite
|
Sign up to set email alerts
|

Big Data Management Algorithms, Deep Learning-Based Object Detection Technologies, and Geospatial Simulation and Sensor Fusion Tools in the Internet of Robotic Things

Abstract: The objective of this systematic review was to analyze the recently published literature on the Internet of Robotic Things (IoRT) and integrate the insights it articulates on big data management algorithms, deep learning-based object detection technologies, and geospatial simulation and sensor fusion tools. The research problems were whether computer vision techniques, geospatial data mining, simulation-based digital twins, and real-time monitoring technology optimize remote sensing robots. Preferred Reporting… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
24
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 56 publications
(24 citation statements)
references
References 123 publications
0
24
0
Order By: Relevance
“…Specifically, questions related to computer ethics and morality issues were found to have a significant positive impact. This highlights the importance of education and awareness campaigns surrounding computer ethics to stimulate interest and participation in the field [5, 6, 42]. The findings demonstrate the dynamic evolution of computer ethics, emphasizing the shift from individual‐centric perspectives to network ethics.…”
Section: Discussionmentioning
confidence: 75%
See 3 more Smart Citations
“…Specifically, questions related to computer ethics and morality issues were found to have a significant positive impact. This highlights the importance of education and awareness campaigns surrounding computer ethics to stimulate interest and participation in the field [5, 6, 42]. The findings demonstrate the dynamic evolution of computer ethics, emphasizing the shift from individual‐centric perspectives to network ethics.…”
Section: Discussionmentioning
confidence: 75%
“…They can identify and understand ethical issues within large data sets, such as detecting harmful content, hate speech, or misinformation [7]. The synergy of multisensor fusion navigation algorithms and feature information‐efficient representation networks can bring a new dimension to the automated analysis of computer ethics issues [5, 6, 43]. By combining sensor data with feature extraction through neural networks, it becomes possible to gain insights into users' digital behavior and its ethical implications.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Authors show that strong intelligence and empathetic behavior in service robots and AI devices can increase their acceptance by consumers. Andronie et al (2023) provided a systematic review of recent literature on the Internet of Robotic Things (IoRT) to explore how big data management algorithms, deep learning-based object detection technologies, and geospatial simulation and sensor fusion tools optimize remote sensing robots. The review identified computer vision techniques, geospatial data mining, simulation-based digital twins, and real-time monitoring technology as important for IoRT.…”
Section: Methodsmentioning
confidence: 99%